Understanding your one-year-old - Gustavus Jones, Sarah, 1961- (Understanding your child series., 2004)
How does a one-year-old's mind and personality develop and grow? How does your role as a parent change when your baby starts to walk, talk and really explore the world around her? How do you support and understand your very young child as his independence increases and he starts to become a toddler, beginning to learn to dress himself, share toys and play with other children. Sarah Gustavus Jones offers guidance, reassurance and sensitive exploration of the central issues you can be aware of as your child's physical and emotional needs develop and change.